Impact of early recognition of potentially malignant oral disorders on the prognosis in people living with HIV. (June 2019) - Anaya-Saavedra, Gabriela; Ramírez-Amador, Velia; Castillejos-García, Itzel; Saeb-Lima, Marcela
Despite the success of combination antiretroviral therapies, people living with HIV (PLWH) are at an increased risk of developing diverse malignancies, including oral cancer. We here present two cases of PLWH where the early diagnosis of potentially malignant disorders in the oral cavity impacted their treatment and survival, remaining free of disease after their complete elimination. These cases demonstrate the importance of oral examinations and tissue biopsies as a part of the close monitoring of PLWH.